2007
DOI: 10.1007/s10620-006-9489-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of a Novel, Water-Soluble Vitamin E Formulation in Malabsorbing Patients

Abstract: In cystic fibrosis (CF), pancreatic insufficiency and a diminished bile acid pool cause malabsorption of important nutrients and dietary components leading to deficiency, poor nutritional status, and oxidative stress. Of particular significance is the malabsorption of fat-soluble nutrients and antioxidants, which are important for normal immune and neurologic function. Patients with CF often are deficient in these compounds despite supplementation with the current standard of care therapy. The objective was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The drinking water of animals was supplemented with vitamin E: “Aqua E” [33] containing 20 IU d-α-tocopherol, 15 mg other tocopherols, and 2 mg tocotrienols per mL. Aqua E has been used to guarantee an equivalent Vitamin E absorption: according to Papas et al (2007), Aqua E showed a better bioavailability in malabsorbing patients compared to conventional based supplements [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drinking water of animals was supplemented with vitamin E: “Aqua E” [33] containing 20 IU d-α-tocopherol, 15 mg other tocopherols, and 2 mg tocotrienols per mL. Aqua E has been used to guarantee an equivalent Vitamin E absorption: according to Papas et al (2007), Aqua E showed a better bioavailability in malabsorbing patients compared to conventional based supplements [33].…”
Section: Methodsmentioning
confidence: 99%
“…Aqua E has been used to guarantee an equivalent Vitamin E absorption: according to Papas et al (2007), Aqua E showed a better bioavailability in malabsorbing patients compared to conventional based supplements [33]. Body weight and food intake were measured weekly, water/vitamin E uptake as an average per cage daily.…”
Section: Methodsmentioning
confidence: 99%
“…However, the review did not include the minimum number of studies (n = 10) for any analysis. Furthermore, while funnel plot asymmetry may indicate publication bias, this is not inevitably the case (Egger 1997). This issue will be considered for a future version of this review provided there is a sufficient number of included studies.…”
Section: Methodsmentioning
confidence: 99%
“…In the attempt to promote liposoluble vitamin absorption, new pharmacologic formulations of vitamin E have been developed. Tocopheryl polyethylene glycol succinate is a hydrosoluble form of vitamin E. This water-soluble formulation showed a marked and statistically significant increase in the absorption of gamma-tocopherol in malabsorbing patients with cystic fibrosis (CF) compared with a classic oil-based formulation [51]. Recently, intestinal absorption of water-soluble vitamin E (tocofersolan) was compared with a water-miscible form in 12 CF or cholestatic children [52].…”
Section: Introductionmentioning
confidence: 99%